The Role Of Digitalization In Developing Entrepreneurial Spirit In Generation Z - Soni, Mohammad; Solihat, Asri; Adiansyah, Adi; Dahlena, Alni; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The application of digital technology can provide space for individuals to develop their entrepreneurial skills, both in educational environments and in the real field. The availability of various digital-based financial applications and platforms makes it easier for them to learn, plan, and make investment decisions. This development is very important in equipping Gen Z to face future economic challenges. The purpose of this study is to analyze the role of digitalization in building an entrepreneurial spirit for generation Z, especially in responding to challenges in the digital era. The research method used is a systematic literature review (SLR) design to document efforts to overcome natural disasters in the context of digitalization of entrepreneurship, by exploring relevant and indexed related literature. Data collection techniques through publish or perish software, then data analysis techniques with vosviewer to analyze novelty data. The results of the analysis identified that the nodes between the roles of digitalization in building an entrepreneurial spirit in generation Z, where there are new opportunities and potential to develop entrepreneurship, especially in a digital context. The digitalization era, if utilized properly in building an entrepreneurial spirit, will also have a good impact. Therefore, digitalization will have an impact on Gen Z's insight in building an entrepreneurial spirit.